Haematobia Le Peletier & Serville 1828 - Sorokina, Vera S.; Pont, Adrian C. (Zenodo, 2010)
Genus Haematobia Le Peletier & Serville, 1828 Haematobia Le Peletier & Serville in Latreille et al ., 1828: 499 (as a subgenus of Stomoxys Geoffroy, 1762). Type-species: Conops irritans Linnaeus, 1758, by designation of Westwood (1840: 140) and validated by I.C.Z.N., Opinion 1008 (1974: 157–158). Haematobia irritans (Linnaeus, 1758) Conops irritans Linnaeus, 1758: 604. Type-locality: not stated (presumably Sweden). Lectotype ♂, LSUK (designated by Pont, 1981a: 169). Siberian records: Middle and South Urals (Zagrebin, 1989: 20; 1992: 60); Sverdlovskaya Oblast’: Serov, Krasnoufimsk, Talizy, Verkhovino (Zagrebin, 1987a: 231); Chelyabinskaya Oblast’, Troizkiy Rayon (Kutuzova, 1993: 74, 75); Tyumenskaya Oblast’, common in forest steppe, rarer in subtaiga and southern taiga (Veselkin, 1966: 783); Kurganskaya Oblast’ (Veselkin, 1989: 11); Baykal-Amur railway (Veselkin, 1981: 371); West and East Siberia (Pont, 1986a: 109). General distribution: Holarctic and Neotropical Regions, also Hawaii. Haematobia thirouxi titillans (Bezzi, 1907) Lyperosia titillans Bezzi, 1907: 454. Replacement name for irritans of Rondani (1862) and Pandellé (1898) in part, not Linnaeus, 1758 (misidentifications). Type-localities: Italy, Parma district, Calabria and the Alps; and France, Landes and Paris. Syntypes ♂ ♀, MZUF, MNHN, 11♂ 2♀, MCSNM (seen), 1♂, BMNH (Pont, 1990: 169), and 1♂, IPP (seen). Siberian records: Chelyabinskaya Oblast’, Troizkiy Rayon (Kutuzova, 1993: 74, 75); Tyumenskaya Oblast’, forest steppe, subtaiga and southern taiga (Veselkin, 1966: 787); Kurganskaya Oblast’ (Veselkin, 1989: 11); Tyumen’ and Omsk (Veselkin, 1972: 270–271); Baykal-Amur railway (Veselkin, 1981: 371); South Tyva (Lake Shara-Nur and River Naryn-gol) (Pridantseva, 1959: 145–155); South Tyva, River Naryn-gol (Pridantseva, 1967: 828); Respublika Tyva (Tamarina & Khromova, 1980: 81); South Siberia (Hörning, 1959: 340); West and East Siberia (Pont, 1986a: 109). General distribution: Palaearctic Region, from Europe east to China, also India (Kashmir). : Published as part of Sorokina, Vera S. & Pont, Adrian C., 2010, An annotated catalogue of the Muscidae (Diptera) of Siberia 2597, pp. 1-87 in Zootaxa 2597 (1) on pages 32-33, DOI: 10.11646/zootaxa.2597.1.1, http://zenodo.org/record/5318926 : {"references": ["Latreille, P. A., Lepeletier, A. L. M., Serville, J. G. A. & Guerin-Meneville, F. E. (1828) Entomologie, ou histoire naturelle des crustaces, des arachnides et des insectes. In: Encyclopedie methodique, ou par ordre des matieres. Histoire naturelle. Insectes. Volume 10 (2). Agasse, Paris, pp. 345 - 832.", "Geoffroy, E. L. (1762) Histoire abregee des insectes qui se trouvent aux environs de Paris; dans laquelle ces animaux sont ranges suivant un ordre methodique. Volume 2. Durand, Paris, 690 pp.", "Linnaeus, C. (1758) Systema naturae per regna tria naturae, secundum classes, ordines, genera, species, cum caracteribus, differentiis, synonymis, locis. 10 th edition. Volume 1. L. Salvii, Holmiae [= Stockholm], 824 pp.", "Westwood, J. O. (1840) Order XIII. Diptera Aristotle. (Antliata Fabricius. Halteriptera Clairv.). In: An introduction to the modern classification of insects; founded on the natural habits and corresponding organisation of the different families. Synopsis of the genera of British insects. Longman, Orme, Brown, Green & Longmans, London, pp. 125 - 154.", "Pont, A. C. (1981 a) The Linnaean species of the families Fanniidae, Anthomyiidae and Muscidae (Insecta: Diptera). Biological Journal of the Linnean Society of London, 15, 165 - 175.", "Zagrebin, A. I. (1989) The peculiarity of ecology of zoophilous flies (Diptera) in the Urals. In: Nikolaeva, N. V. (Ed.), Insects in the biogeocenozes of the Urals. Vsesoyuznoe entomologicheskoe obshchestvo Urala (Ural Division), Sverdlovsk [= Yekaterinburg], pp. 20 - 21. [In Russian.]", "Zagrebin, A. I. (1992) The zonal distribution of pasture flies (Diptera) in the Middle and Southern Urals. In: Nikolaeva, N. V. (Ed.), Insects in natural and anthropogenic biogeocenozes of the Urals. Nauka, Yekaterinburg, pp. 59 - 60. [In Russian.]", "Zagrebin, A. I. (1987 a) On the fauna of pasture flies of the family Muscidae (Diptera) in the Urals. In: Cherepanov, A. I. (Ed.), Ecology and geography of arthropods in Siberia. Nauka (Siberian Division), Novosibirsk, pp. 231 - 233. [In Russian.]", "Kutuzova, T. M. (1993) Specific structure and dynamics of a number of flies in the forest-steppe of the Transurals connected with large horned livestock. In: Utochkin, A. S. (Ed.), Fauna and ecology of insects of the Urals. Perm State University, Perm, pp. 71 - 81. [In Russian.]", "Veselkin, G. A. (1966) Flies (Diptera), satellites of domestic animals and man, in the southern part of the Tyumen' Region. Entomologicheskoe Obozrenie, 45, 779 - 792. [In Russian.] [English translation in Entomological Review, Washington, 45 (4), 439 - 447.]", "Veselkin, G. A. (1989) Specific structure and ecology of flies (Diptera, Cyclorrhapha) that are parasitic on domestic animals in the Kurgan area. In: Nikolaeva, N. V. (Ed.), Insects in the biogeocenozes of the Urals. Vsesoyuznoe entomologicheskoe obshchestvo Urala (Ural Division), Sverdlovsk [= Yekaterinburg], pp. 10 - 11. [In Russian.]", "Veselkin, G. A. (1981) Fauna and ecology of horn flies (Muscidae) from the territory of the Baikal-Amur railway. Parazitologiya, 15, 371 - 374. [In Russian, with English summary.]", "Pont, A. C. (1986 a) Family Muscidae. In: Soos, A. & Papp, L. (Eds), Catalogue of Palaearctic Diptera. Volume 11. Scathophagidae - Hypodermatidae. Akademiai Kiado, Budapest, pp. 57 - 215.", "Bezzi, M. (1907) Die Gattungen der blutsaugenden Musciden. (Dipt.) Zeitschrift fur systematische Hymenopterologie und Dipterologie, 7, 413 - 416.", "Rondani, C. (1862) Dipterologiae Italicae prodromus. 5. Species italicae ordinis Dipterorum in genera characteribus definita, ordinatim collectae, methodo analitica distinctae, et novis vel minus cognitis descriptis. Pars Quarta. Muscidae Phasiinae - Dexinae - Muscinae - Stomoxidinae. Grazioli, Parmae [= Parma], 239 pp.", "Pandelle, L. (1898) Etudes sur les Muscides de France. III e partie. [Part.] Revue d'Entomologie, Caen, 17 (Supplement), 33 - 64.", "Pont, A. C. (1990) Muscidae. In: Townsend, B. C. (Ed.), A catalogue of the types of bloodsucking flies in the British Museum (Natural History). Occasional Papers on Systematic Entomology, 7, 163 - 170.", "Veselkin, G. A. (1972) Biological principles of the control of synanthropic Diptera in Western Siberia. Proceedings of the 13 th International Congress of Entomology 1968, 3, 270 - 271.", "Pridantseva, E. A. (1959) A contribution to the biology of Lyperosia titillans Bezzi (Diptera, Muscidae), an intermediate host of the nematode Parabronema skrjabini Rass. Entomologicheskoe Obozrenie, 38, 145 - 155. [In Russian, with English summary.] [English translation in Entomological Review, Washington, 38 (1), 129 - 138.]", "Pridantseva, E. A. (1967) The fauna of pasture flies (Diptera) connected with camels in South Tuva. Entomologicheskoe Obozrenie, 46, 827 - 834. [In Russian.] [English translation in Entomological Review, Washington, 46, 491 - 494.]", "Tamarina, N. A. & Khromova, L. A. (1980) Fauna and ecology of pasture flies (Diptera) - intermediate hosts of the parasitic nematodes in the Tuva Autonomous Republic. Entomologicheskoe Obozrenie, 59, 79 - 85. [In Russian, with English summary.] [English translation in Entomological Review, Washington, 61 (4), 141 - 147.]", "Horning, B. (1959) Fliegen als Uebertrager parasitarer Wurmer. In: Internationales Symposium uber schadliche Fliegen im Lebensbereich der Menschen. Zeitschift fur angewandte Zoologie, 46, 338 - 342."]}